Скляні вироби із розкопок у колишньому Бернардинському костелі в Дубні - Гупало, В.; Лосик, М. (Інститут українознавства ім. І. Крип'якевича НАН України, 2009)
Collection of glass artifacts, which was found during excavations in town of Dubno is examined at the article. Basing on chemical analysis, the authors conclude, that most of these products are made of potassium-calcium-flint glass. They also present hypothesis, that glass production in Halychyna and Volhyn’ during XVII–XVIII centuries have local character. But searching for concrete center of this production is still a task for next explorations.